Pengaruh Konsentrasi Bubuk Kakao (Theobroma cacao L.) terhadap Karakteristik Krim Kunyit Daun Asam - Anggelo, Dicki Cahya Putra; Mulyani, Sri; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 3 (2021): September, 2021)
People are increasingly aware of the dangers of using harmful chemicals in cosmetics. One of the herbal ingredients that can be used in the manufacture of cosmetics is turmeric, tamarind leaves and cocoa powder which are applied in making creams. The purpose of this study was to know the effect of the concentration of cocoa powder on the characteristic of tumeric tamarind cream and to obtain the concentration of cocoa powder that produces cream of turmeric extract and tamarind leaves with the best characteristics.This study used a non-factorial randomized block design with 6 concentration levels of 0%, 3%, 6%, 9%, 12%, and 15%. The variables observed in the cream were homogenity, viscosity, pH, spreadability, separation ratio, adhesion, color intensity, and total phenol. The data were analyzed by Analysis of Variance , if the treatment had an effect, it was continued with Duncan's test. The results of this study showed that the concentration of cocoa powder in cream with active ingredients of turmeric and tamarind had a significant effect on viscosity, adhesion, spreadability, total phenol, cream brightness level (L*), but had no effect on pH, separation ratio and redness level ( a*) and the degree of yellowness (b*) of cream. The treatment of cocoa powder on sour cream turmeric leaves with a concentration of 9% met the criteria for the characteristics of the cream, namely: homogeneous cream, 5.43 to 4.46 cm spreadability, 6.78 to 9.05 second adhesion, pH 6, 36 to 6.46, a viscosity of 11,3 to 24,0, and a separation ratio of 1. Keywords : cocoa powder, tamarind leaves, turmeric, cream characteristics.